2007
DOI: 10.1152/ajpgi.00536.2006
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin selectively reduces mechanosensitivity of upper gastrointestinal vagal afferents

Abstract: Ghrelin is a peptide released from gastric endocrine cells that has an orexigenic effect via a vagal pathway. Here we determine the effect of ghrelin on mechanosensitivity of upper-intestinal vagal afferent fibers in ferret and mouse. The responses of gastroesophageal vagal afferents to graded mechanical stimulation were determined in vitro before and during application of ghrelin to their peripheral endings. Three types of vagal afferent were tested: tension receptors responding to circumferential tension, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 67 publications
7
66
0
3
Order By: Relevance
“…On the basis of the data in the previous reports [21][22][23][24][25], it is conceivable that postprandial elevation of plasma active GLP-1 concentration suppresses ghrelin secretion via the vagal nerve system. Nevertheless, a pharmacological amount of GLP-1 was needed to lower plasma ghrelin in the patient with PWS.…”
Section: Biochemical Measuresmentioning
confidence: 97%
“…On the basis of the data in the previous reports [21][22][23][24][25], it is conceivable that postprandial elevation of plasma active GLP-1 concentration suppresses ghrelin secretion via the vagal nerve system. Nevertheless, a pharmacological amount of GLP-1 was needed to lower plasma ghrelin in the patient with PWS.…”
Section: Biochemical Measuresmentioning
confidence: 97%
“…Experiments in which the antral mucosa was separated from the underlying muscle, a procedure that abolishes vago-vagal reflexes, suggest that mucosal mechanoreceptors may discriminate particles by size and regulate their passage into the duodenum [18]. Mucosal afferents may also be involved in the control of satiety, as their mechanosensitivity is enhanced by the satiety hormone, leptin, and reduced by the feeding hormone, ghrelin, both of which are released from gastric enteroendocrine cells that are in close proximity to the gastric mucosal afferent endings [19,20]. In humans, ghrelin signalling to hypothalamic feeding centers is via the vagus [21].…”
Section: Structural and Functional Characteristics Of Vagal Afferent mentioning
confidence: 99%
“…Ghrelin, an orexigenic hormone secreted from the stomach, was soon after its discovery hypothesized to be a prokinetic agent, due to its homology to the motilin. Investigation of ghrelin physiology has demonstrated that ghrelin is secreted by gastric endocrine cells into the bloodstream, providing local effects by modulating the information up-flow through the vagus nerve to the brain stem nuclei and hypothalamus [17]. Additionally to this ghrelin may also stimulate the production of growth hormone.…”
Section: Role Of Afferent Nerves In Gastroduodenal Adaptationmentioning
confidence: 99%